2017
DOI: 10.24095/hpcdp.37.8.01
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis knowledge translation for young adults: new directions for prevention programs

Abstract: Introduction: Osteoporosis prevention is heavily reliant on education programs, which are most effective when tailored to their intended audience. Most osteoporosis prevention education is designed for older adults, making application of these programs to younger adults difficult. Designing programs for young adults requires understanding the information-seeking practices of young adults, so that knowledge about osteoporosis can be effectively translated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For example, a previous systematic review reported that enhanced levels of weight bearing physical activity, acting together with dietary calcium intake, is the most beneficial to PBM acquisition [3]. However, engagement of adolescents and young adults with such lifestyles depends upon their knowledge of factors associated with good bone health and a motivation to lead healthy lives [8]. A recent study by our group examined factors that impact participation in sporting activity among young people, finding that a number of barriers and enablers exist [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous systematic review reported that enhanced levels of weight bearing physical activity, acting together with dietary calcium intake, is the most beneficial to PBM acquisition [3]. However, engagement of adolescents and young adults with such lifestyles depends upon their knowledge of factors associated with good bone health and a motivation to lead healthy lives [8]. A recent study by our group examined factors that impact participation in sporting activity among young people, finding that a number of barriers and enablers exist [9].…”
Section: Introductionmentioning
confidence: 99%
“…Because osteoporosis is a preventable progressive metabolic disease, [ 23 ] reducing the future prevalence of osteoporosis requires reducing reduction in the risk of future osteoporosis in young adults. [ 24 ] Therefore, management and early screening of osteoporosis or osteopenia in women in their 20s and 30s are important, as this is the golden period for osteoporosis prevention.…”
Section: Discussionmentioning
confidence: 99%
“…As young adults are not concerned about future disease risk, it is necessary to raise awareness of osteoporosis to increase participation in preventive action. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, designing education programs for youths requires understanding on their information-seeking behaviours to ensure successful knowledge transfer [57]. One example is through the effective use of traditional and emerging social networks [57].…”
Section: Perspectivesmentioning
confidence: 99%
“…However, designing education programs for youths requires understanding on their information-seeking behaviours to ensure successful knowledge transfer [57]. One example is through the effective use of traditional and emerging social networks [57]. To address the lack of concern about future disease risk, the health promotion messages could interlace with their current interests in appearance and physical fitness.…”
Section: Perspectivesmentioning
confidence: 99%